2021
DOI: 10.4048/jbc.2021.24.e24
|View full text |Cite
|
Sign up to set email alerts
|

HOXD Antisense Growth-Associated Long Noncoding RNA Promotes Triple-Negative Breast Cancer Progression by Activating Wnt Signaling Pathway

Abstract: Purpose Triple-negative breast cancer (TNBC) is the most lethal subtype of breast cancer owing to high heterogeneity, aggressive nature, and lack of treatment options, which has a substantial deleterious effect on patients' lives. HOXD antisense growth-associated long noncoding RNA (lncRNA) (HAGLR) plays tumor-promoting roles in many cancers. In this study, we aimed to explore the role of HAGLR in TNBC. Methods Quantitative real-time polymerase chain reaction assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As proof, lncRNA DILA1 downregulation promoted TAM sensitivity in BC 33 . LncRNA HAGLR was previously confirmed as an oncogene in several human malignancies, including BC 13,16 . However, little is known about the role of HAGLR involved in TAM resistance in BC.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…As proof, lncRNA DILA1 downregulation promoted TAM sensitivity in BC 33 . LncRNA HAGLR was previously confirmed as an oncogene in several human malignancies, including BC 13,16 . However, little is known about the role of HAGLR involved in TAM resistance in BC.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study has been demonstrated that HAGLR takes an essential role to be involved in BC progression 16 . Hence, we firstly examined the expression patterns of HAGLR in the cellular level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It induces a cancer cell cycle, proliferation, apoptosis, tumorigenic angiogenesis, and metastasis ( Sokół et al, 2017 ). Upregulation of SRSF1 activates the Wnt pathway, promoting tumor growth ( Malakar et al, 2017 ; Zhang et al, 2021 ), which may be related to the accumulation of β-catenin proteins ( Fu et al, 2013 ). Glycogen synthase kinase-3β is a serine/threonine kinase that participates in various signaling pathways including Wnt/β-catenin.…”
Section: Discussionmentioning
confidence: 99%